Evaluation of access to care issues in patients with breast cancer. (1st January 2021) - Brown, Carolyn M.; Richards, Kristin M.; Vohra, Yogesh; Kanu, Chisom; Stevens, Laura; Sasane, Rahul; Balu, Sanjeev; McAneny, Barbara
Abstract: Aims: System-level efforts have been deployed to improve oncology care and access while reducing utilization and costs. Understanding the nature of access to care from the perspective of patients themselves is an unmet need. This study examined access to care in a population of women with breast cancer and its relationship to overall patient satisfaction. Materials and methods: Patients with breast cancer from six oncology clinics in five states completed a survey during routine office visits. Access to care (higher scores indicated increasing access barriers), overall patient satisfaction, and patient demographic/clinical characteristics were measured. The relationships between access (composite and factor scores) and satisfaction were assessed using multivariable analyses controlling for age (the only significant characteristic from bivariate analyses). Results: A total of 180 patients completed the survey. Factor analysis of access to care items revealed an 8-factor measure – Insurance, Health System, Emotional, Holistic Treatment, Family Support, Knowledge/Understanding, Information Quality, and Financial Support – with high reliability (Composite: Cronbach alpha = 0.93; Factors: Cronbach alpha range = 0.85–0.91). Access composite score was moderately low (mean = 1.90), indicating an overall low level of access barriers, and overall patient satisfaction was high (mean = 4.59). The composite score ( p  < .001) and the Health System and Knowledge/Understanding factors ( p  < .01) were significant and negative predictors of overall satisfaction. Limitations: Study sites were high functioning clinics and all, but one, are Oncology Care Model practices. Thus, the scope of access to care issues for patients of under-resourced clinics might not be well addressed. Conclusions: Access to care overall and by factor was significantly predictive of patient satisfaction with care. In addition, access to care factors varied across several demographic and clinical characteristics. Future strategies that address access to care challenges should consider these modifiable, patient-centric, and system-based issues.